2009
DOI: 10.1101/gr.086512.108
|View full text |Cite
|
Sign up to set email alerts
|

The difficulty of avoiding false positives in genome scans for natural selection

Abstract: Several studies have found evidence for more positive selection on the chimpanzee lineage compared with the human lineage since the two species split. A potential concern, however, is that these findings may simply reflect artifacts of the data: inaccuracies in the underlying chimpanzee genome sequence, which is of lower quality than human. To test this hypothesis, we generated de novo genome assemblies of chimpanzee and macaque and aligned them with human. We also implemented a novel bioinformatic procedure f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 24 publications
(45 reference statements)
5
86
0
Order By: Relevance
“…These results suggest that even if the proportion of misaligned codon sites is small, they cause significant overestimation of the d N /d S ratio for the entire alignment of codon sequences constructed by reverse-translating aligned amino acid sequences (Wong et al, 2008;Mallick et al, 2009;Schneider et al, 2009). These codon sites may also be falsely identified as positively selected (Vamathevan et al, 2008;Wong et al, 2008;Mallick et al, 2009;Schneider et al, 2009;Fletcher and Yang, 2010).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…These results suggest that even if the proportion of misaligned codon sites is small, they cause significant overestimation of the d N /d S ratio for the entire alignment of codon sequences constructed by reverse-translating aligned amino acid sequences (Wong et al, 2008;Mallick et al, 2009;Schneider et al, 2009). These codon sites may also be falsely identified as positively selected (Vamathevan et al, 2008;Wong et al, 2008;Mallick et al, 2009;Schneider et al, 2009;Fletcher and Yang, 2010).…”
Section: Resultsmentioning
confidence: 87%
“…However, the d N /d S ratio is known to be inflated at mis-aligned codon sites (Wong et al, 2008;Mallick et al, 2009;Schneider et al, 2009). It has also been reported that as more non-homologous codons are aligned, more amino acid sites are falsely identified as positively selected (Vamathevan et al, 2008;Wong et al, 2008;Mallick et al, 2009;Schneider et al, 2009;Fletcher and Yang, 2010). The purpose of the present study was to examine the effect of reverse-translating aligned amino acid sequences on the estimation of d N /d S ratio, through a large-scale analysis of protein-coding nucleotide sequences from vertebrate species.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of a single codon site with the occurrence of multiple nonsynonymous substitutions in the entire sequence sometimes appeared to be sufficient for erroneously detecting positive selection. This method was also found to produce spurious results of positive selection when estimates of d N /d S were inflated due to episodes of GC-biased gene conversion (Berglund et al, 2009;Galtier et al, 2009;Hurst, 2009) and each of sequencing, annotation, and alignment errors (Mallick et al, 2009;Schneider et al, 2009;Fletcher and Yang, 2010). From the analysis of rhodopsins in vertebrates, it was shown that positively selected sites identified by the branch-site method mostly disagreed with experimentally determined adaptive sites (Nozawa et al, 2009b).…”
Section: Methods For Detecting Recurrent Natu-ral Selection Using DIVmentioning
confidence: 99%
“…Kelley et al (2006) also conducted computer simulation based on Tajima's D and found that the false-discovery rate can be high when positive selection is weak, the fraction of truly positively selected loci is small, and the fraction of test statistic values considered as evidence for positive selection is large. Little overlap among results from different studies It has been reported that the fraction of overlap between positively selected regions identified in different studies is generally small (Mallick et al, 2009). When 713 positively selected genes in human identified by the iHS test (Voight et al, 2006) were compared with 90 positively selected genes identified by the LDD test (Wang et al, 2006), only 9 genes were shared between the two results .…”
Section: Composite-likelihood Ratio Testmentioning
confidence: 99%
See 1 more Smart Citation